An analytical survey on college students experiences: the quality of efforts exerted and their perception of the gains the case of PPP/ITM American degree program / Faridahanim Mohd Jaafar, Zaini Abdullah and Jamaliah Mohd Khalili - Mohd Jaafar, Faridahanim; Abdullah, Zaini; Mohd Khalili, Jamaliah (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 2000)
In an effort to improve the quality of students' outcomes, applied and analytical research was conducted on the students experiences in the university. The Center of Preparatory Studies (The American Degree Program, PPP/UiTM) was selected. The Students Experiences Questionnaire was administered to some 400 students during the second semester of 1998. The survey focused on the following areas: college environment; institutional effectiveness; estimated gain on a variety of personal and developmental indicators; extent of participation in college activities, and the quality of efforts exerted. Key findings, based on completed questionnaires of 236 students, included the following: 1) Generally, the survey participants found that the quality of student services were satisfactory. The survey also indicated that they had made their greatest gain in acquiring knowledge and skills relevant to the field of Science, Mathematics and Technology. 2) Writing activities were a prominent part of the university experience for respondents. 3) It was also noted that less than 30% of the respondents checked out books from the library and only about 38% used the library. 4) Over 60% of the respondents often use information they had learned in science to understand some aspects of their work. 5) 70% and more of the respondents had indicated they have developed the ability to learn on their own. 6) Less than 40% participated in students clubs and organizations. The study provides a detailed descriptive statistics of the survey. The quality of efforts exerted by students in the areas of Science and Mathematics and the estimated gains they have perceived were statistically analyzed for the reliability of the variables and its correlation effect.